Does hyperthermic intraperitoneal chemotherapy influence the rate of infective complications and change the pattern of infectious agents in patients undergoing cytoreductive surgery for peritoneal carcinomatosis? - Mercan, Umit; Ersen, Ogun; Yuksel, Cemil; Ekrem Unal, Ali (Annals of Medical Research, 2021)
Aim: When CRS, in which complex surgical procedures are applied combined with HIPEC in which high dose cytotoxic agents are applied, many serious postoperative complications, especially infection-related complications, may develop in the patient group with peritoneal carcinomatosis whose general condition is impaired. In this study, it was aimed to investigate the effect of HIPEC application after SRC on infection rates and microbial agent spectrum alone.Materials and Methods: Between January 2012 and January 2020, one thousand six hundreds forty eight patients diagnosed with peritoneal carcinomatosis were scanned from hospital database and two hundred thirty-five eligible patients were included in the study. Demographic and clinical data, perioperative results and culture results were analyzed by grouping the patients as HIPEC and non-HIPEC.Results : It has been found that the incidence of surgical site infections was significantly higher in HIPEC group. (23.6%vs11.5%p=0.011).When the culture results were analyzed. The number of patients with E.coli (13.7% vs 5.7% p = 0.001), Klebsiella pneumoniae (9.9% vs 2.8% p = 0.001) and Pseudomonas aeruginosa (2.2% vs 0.9% p = 0.034) growth was significantly higher in the HIPEC group.Conclusions: It has been found that HIPEC application not only increases the infection rates but also expands the potential pathogen spectrum. Prediction of possible pathogens responsible for postoperative infections may affect the choice of prophylactic and ultimate treatment and so the risk of developing morbidity and mortality which may result from a possible septic progression, can be minimized with an effective antimicrobial therapy.
Keywords: Carcinomatosis; cytoreductive surgery; infections